2020
DOI: 10.1002/mnfr.202000312
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin Activates AMPK/PGC‐1α/Nrf2 Cascade in Mice: The Potential Protective Effect against Prenatal Stress

Abstract: ScopePrenatal stress is closely associated with poor health outcomes for offspring, yet the specific mechanisms and effective interventions remain limited.Methods and ResultsIn the present study, both male and female rat offspring exposed to prenatal restraint stress (PRS) are confirmed to have impaired spatial learning and memory, accompanied by reduced AMP‐activated protein kinase (AMPK) activity and decreased protein expression of mitochondrial biogenesis and antioxidant pathways in the hippocampus. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…3 It has been demonstrated to exhibit bioprotective effects such as reduction of oxidative stress 4 and anti-inflammatory and anti-tumor activities. 5,6 The antioxidant activity of PU is due to the high hydroxylation structure. 7,8 Gil et al 3 reported that PU contributed 50% antioxidant activities of pomegranate juice.…”
Section: Introductionmentioning
confidence: 99%
“…3 It has been demonstrated to exhibit bioprotective effects such as reduction of oxidative stress 4 and anti-inflammatory and anti-tumor activities. 5,6 The antioxidant activity of PU is due to the high hydroxylation structure. 7,8 Gil et al 3 reported that PU contributed 50% antioxidant activities of pomegranate juice.…”
Section: Introductionmentioning
confidence: 99%
“…AMPK is one of the crucial energy sensors which could modulate mitochondrial biogenesis through activating NRF2 in this phosphorylated status [ 35 ]. Once NRF2 is activated, it could translocate into cell nucleus and transcriptionally activate a great many antioxidant genes that are responsible for mitochondrial fusion and fission [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings confirmed that administration of EA prevents cognitive impairment through attenuation of the brain lipid peroxidation and prevented waning of the superoxide dismutase (SOD), glutathione (GSH), and catalase (CAT) activity in streptozotocin-induced rats ( Kumar and Bansal, 2018 ). Cao et al (2020) revealed that ellagitannin activates AMP-activated protein kinase (AMPK) to ameliorate oxidative stress by activation of NF-E2-related factor (Nrf2)-mediated phase II antioxidant enzymes. In such a manner, EA is involved not only in the management of endogenous and exogenous sources of reactive oxygen species (ROS), but also involved in antioxidant defense mechanisms.…”
Section: Molecular Mechanism Of Therapeutic Properties Of Ellagic Aci...mentioning
confidence: 99%
“…Meanwhile, urolithin A activates mitochondrial autophagy to exert neuroprotective effects through activation of the SIRT1/mTOR signaling pathway, which aids in preventing D-galactose-induced brain aging ( Chen et al, 2019 ). Cao et al (2020) found that punicalagin regulates mitochondrial biogenesis by activating AMPK/peroxisome proliferator-activated receptor gamma coactivator 1-α (PGC-1α) signaling, thereby preventing cognitive dysfunction. Additionally, mitochondrial respiratory dysfunction is also the main cause of ROS overproduction and treatment of EA can prevent the decrease of mitochondrial succinate dehydrogenase activity in the rat brain caused by 3-nitropropionic acid, thus protecting mitochondrial functions ( Sharma et al, 2021 ).…”
Section: Molecular Mechanism Of Therapeutic Properties Of Ellagic Aci...mentioning
confidence: 99%